Meaningful Participation in Local Regulation Making in Indonesia: A Study of Legislative Law: Meaningful Participation pada Pembuatan Peraturan Daerah di Indonesia: Sebuah Kajian Hukum Perundang-undangan - Rizqi, Alda Rifada (Universitas Muhammadiyah Sidoarjo, 2022)
The meaningful participation aspect is one of the conceptions born after the Constitutional Court's decision regarding job creation law. It is carefully considered, as well as the right to obtain answers and justifiable reasons for the aspirations that have been conveyed. This study examines the application of meaningful participation in forming Regional Regulations. This research is normative legal research with a concept and statutory approach. The research results confirm that meaningful participation must also be applied in preparing regional regulations as part of the legislation. In this case, meaningful participation in the drafting of Regional Regulations must also be proportional and meaningful in taking into account the dimensions and aspects of local wisdom in the regions. In a further application, the idea of meaningful participation needs to be strengthened in preparing regional regulations and regional legal products by emphasizing the meaningful participation aspect in the Permendagri regional legal products. That is so that the idea of meaningful participation can be adhered to by the regions in drafting regional legal products, particularly in drafting regional regulations.